Transformation Management Islamic Institute Becomes a World-Class Institute: Strategy Planning and Implementation - Yetty Faridatul Ulfah (Al-Hayat: Journal of Islamic Education, 2021)
One of the fundamental challenges for education in the era of globalization is that educational institutions must make changes or transformations. This study aims to analyze 1) the transformation of the management of IIM Surakarta into a World-Class Islamic Institute, 2) the strategy in the strategic plan of IIM Surakarta, 3) the implementation of the strategic plan IIM Surakarta. This research approach is descriptive qualitative by applying the case study method at IIM Surakarta. Data were collected using observation, in-depth interviews, and document studies. The results of this study reveal that. 1) The management aspect of the transformation of IIM Surakarta into a World-Class Islamic Institute includes planning, organizing, implementing and evaluating; 2) Strategy is made by conducting a SWOT analysis, and 3) Implementation of the Strategic Plan of IIM Surakarta includes two things, namely setting goals and preparing annual strategic programs.